Small Extracellular Vesicles: Functions and Potential Clinical Applications as Cancer Biomarkers - Wang, Yi; Zhao, Ruichen; Jiao, Xueqiao; Wu, Longyuan; Wei, Yuxuan; Shi, Fuxiu; Zhong, Junpei; Xiong, Lixia (Life (Basel, Switzerland), 2021)
Cancer, as the second leading cause of death worldwide, is a major public health concern that imposes a heavy social and economic burden. Effective approaches for either diagnosis or therapy of most cancers are still lacking. Dynamic monitoring and personalized therapy are the main directions for cancer research. Cancer-derived extracellular vesicles (EVs) are potential disease biomarkers. Cancer EVs, including small EVs (sEVs), contain unique biomolecules (protein, nucleic acid, and lipids) at various stages of carcinogenesis. In this review, we discuss the biogenesis of sEVs, and their functions in cancer, revealing the potential applications of sEVs as cancer biomarkers.